Pengabdian Masyarakat International Workshop Kemandirian Anak-Anak Penyandang Disabilitas dalam Daily Living (Aku Bukan Sampah) Bersama SRC Holland untuk Masyarakat Indonesia - Chandra Lukita; Amroni Amroni; Aan Kanivia; Lena Magdalena; Ridho Taufiq Subagio; Turini Turini; Agus Sevtiana; Wiwiek Nurkomala Dewi (Pusat Riset dan Inovasi Nasional, 2022)
Children with disabilities in Indonesia still face various challenges in achieving independence in everyday life. Special attention is needed to provide adequate support so that they can overcome these obstacles and achieve their rights with dignity. The main focus of this international PkM activity is to introduce innovative methods and strategies that can increase their independence, with the main message